(untitled) (Global Journal of Human-Social Science, 2022)
Lorraine Hansberry in the character of Mama in Raisin in the Sun presents positive solutions for feministic issues She has proved that God is the ultimate solution for life s problems Mama is blessed with a spirit of love and deep faith which enables her to live a life of self sacrifice free of grudges and bitterness Her total surrender and the unshakable faith are grounded in the faithfulness of God and the immutability of His word She suffers pain but her faith in God enables her to deal with pain in such a way that it does not make her bitter but makes her better